Pembelajaran PAI Berbasis Problem Based Learning di SMAN 1 Pamekasan - Rudiyanto Rudiyanto; Nuris Irmayanti; Sayati Sayati; Sukron Makmun (Ideas Publishing, 2022)
Problem-based learning is a learning that presents various problems carried out by teachers in order to improve students ability to think practically, and logistics to find alternative problem solving systematically in order to improve scientific attitudes. The objectives of this research are: first, to describe the teachers steps in implementing problem-based PAI learning at SMAN 1 Pamekasan. Second, describe the inhibiting and supporting factors of problem based learning PAI at SMAN Pamekasan. This study uses a qualitative approach, with the type of descriptive research. Data was collected by means of interviews, observation and documentation. Data analysis by performing data reduction, data presentation and data leveraging. The data obtained check the validity of the data by adding participation, triangulation of sources and methods. The results of the study show that: first, the teachers steps in implementing problem-based learning PAI are: a) The teacher conveys the material and the purpose of the indicators, b) the teacher sets the rules and values ​​in the implementation of learning, c) the teacher forms several groups and asks them to read the topic of the lesson, d) the teacher gives a problem or conflict and asks to educate to find the answer to each group, e) the teacher becomes the facilitator of the discussion, f) the teacher appoints groups for presentations in turn, g) the teacher concludes the answers that the teacher hears from the discussion activities. Second, the inhibiting factors include a) lack of time in one meeting, b) IQ of different students, c) student background, d) lack of facilities and infrastructure, such as the availability of references, the practice of tools in the laboratory, broken chairs. While the supporting factors include a) collaboration between students and teachers, b) the activity of teachers and students. Problem based learning adalah suatu pembelajaran yang menyuguhkan berbagai situasi bermasalah yang dilakukan oleh guru demi meningkatkan kemampuan siswa untuk berpikir praktis, dan logis untuk menemukan alternatif pemecahan masalah melalui eksplorasi data secara empiris dalam rangka menumbuhkan sikap ilmiah. Tujuan dalam penelitan ini yaitu pertama, mendiskripsikan langkah guru dalam mengaplikasikan pembelajaran PAI berbasis problem based learning di SMAN 1 Pamekasan. Kedua, mendiskripsikan faktor penghambat dan pendukung pembelajaran PAI berbasis problem based learning di SMAN Pamekasan. Penelitian ini menggunaan pendeatan kualitatif dengan jenis penelitian desriptif. Pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi. Analisis data dengan melakukan reduksi data, penyajian data, dan verifikasi data. Data yang diperoleh dicek keabsahan data dengan perpanjangan keikutsertaan, triangulasi sumber, dan metode. Hasil penelitian menunjukkan bahwa: pertama, langkah guru dalam penerapan pembelajaran PAI berbasis problem based learning, di antaranya ialah: a) guru menyampaikan materi dan tujuan indikator, b) guru menetapkan peraturan dan nilai dalam pelaksanaan pembelajaran, c) guru membentuk beberapa kelompok dan menyuruh untuk membaca topik pelajaran, d) guru memberikan suatu permasalah atau konflik dan menyuruh berdiskusi mencari jawabnnya kepada setiap kelompok, e) guru menjadi fasilisator berjalannya diskusi, f) guru menunjuk kelompok untuk presentasi secara bergantian, g) guru menyimpulkan jawaban yang guru dengar kegiatan diskusi. Kedua, faktor penghambatnya diantaranya ialah: a) kurangnya waktu dalam sekali pertemuan. b) IQ siswa yang berbeda, c) background siswa, d) kurangnya sarana dan prasarana, seperti ketersediaan referensi, alat-alat praktik di laboratarium, kursi yang rusak. Sedangkan fator pendukung di antaranya ialah a) terjalinnya kerja sama antara siswa dan guru, b) keaktifan guru dan siswa.